Phytochemical composition and antioxidant activity of two species related to family Arecaceae - Naglaa I Afifi; Abeer S Moawad; Mona H Hetta; Rabab M Mohammed (Faculty of Pharmacy, Mahidol University, 2022)
Several studies have focused on the biological and chemical properties of different species of the family Arecaceae. Isolation and characterization of the phytochemicals of Archontophoenix alexandrae (Wendl. & Drude) and Dictyosperma album (Bory) H.Wendl & Drude ex Scheff. leaves (family Arecaceae) and determination of their total phenolics, flavonoids contents and antioxidant activity were investigated in this study. Chromatographic and spectral techniques were used for the phytochemical investigation. Total phenolics content was estimated using Folin-Ciocalteu method, total flavonoids content was determined using AlCl3 assay, while antioxidant activity was estimated using DPPH and reducing power assays. Nine compounds; stigmasterol (1), β-sitosterol (2), tricin (3), luteolin (4), quercetin (5), β-sitosterol-β-D-glucoside (6), ent-epicatechin-(2α→7, 4α→8)-ent-catechin (7), rutin (8) and orientin (9) were isolated and identified. Their structures were established based on spectral techniques (UV, 1H, 13C and 2D-NMR). The antioxidant activity of Dictyosperma album leaves is higher than that of Archontophoenix alexandrae leaves. This work enriched the phytochemical data of Archontophoenix alexandrae (Wendl. & Drude) and Dictyosperma album (Bory) H.Wendl & drudeex. Scheff and their leaves may be a potential antioxidant drug.